PENERAPAN AKAD MURABAHAH PADA PEMBIAYAAN UTSMAN DI PT. BANK PEMBIAYAAN RAKYAT SYARIAH (BPRS) JAM GADANG SEBAGAI UPAYA PENINGKATAN PEREKONOMIAN MASYARAKAT KOTA BIKITTINGGI - Aulia br Surbakti, Syafirah; Azheri, Busyra; Fauzi, Wetria (Penerbit Lafadz Jaya, 2024)
Financing is a primary service offered by Islamic banks, including the Utsman Financing Program at Jam Gadang Islamic Rural Bank (BPRS). This program employs the murabahah contract and does not require collateral. The implementation procedures for the Murabahah Contract have been regulated in the DSN MUI Fatwa No: 04/DSN-MUI/IV/2000. This study aims to evaluate the application of the Murabahah Contract in Utsman Financing and assess the implications of the Fatwa. An empirical juridical methodology was used. The findings reveal that in practice, the wakalah and murabahah contracts are often executed simultaneously, which violates the transaction requirements as the traded object is not fully owned by the contracting parties. Additionally, setting prices and profits for goods not fully owned by the bank and customers also contradicts Sharia principles, thus rendering the transactions invalid.